ENHANCING SPINAL ANESTHESIA WITH DEXMEDETOMIDINE: A PROSPECTIVE STUDY ON PROLONGING ANALGESIA AND REDUCING OPIOID REQUIREMENTS IN INFRA UMBILICAL SURGERIES - VIJAY, YASH; HUSSAIN, AKIL; SHEKHAWAT, DEVASHISH SINGH (International Journal of Current Pharmaceutical Research, 2025)
Objective: Pain management in surgical settings poses significant challenges, particularly in minimizing opioid use due to associated risks. Dexmedetomidine, a selective α2-adrenergic agonist, has shown promise as an adjunct in spinal anesthesia to enhance analgesic and anesthetic effects. Methods: This prospective, randomized, double-blind study involved 60 patients undergoing infraumbilical surgeries, divided into two groups. Group D received intravenous dexmedetomidine, while Group C received a saline placebo. We assessed the duration of sensory and motor blocks, sedation levels, and the time to first postoperative analgesia request. Results: Group D exhibited significantly longer durations of sensory and motor blocks, higher sedation scores, and extended time before requesting postoperative analgesia compared to Group C. These results suggest improved anesthetic quality and pain control with dexmedetomidine. Conclusion: Intravenous dexmedetomidine enhances spinal anesthesia by prolonging block durations and improving sedation, potentially decreasing the need for postoperative opioids. This supports its use as an effective adjunct in anesthesia, contributing to safer, more effective pain management strategies.